2022
DOI: 10.1088/1742-6596/2383/1/012030
|View full text |Cite
|
Sign up to set email alerts
|

Blades layout and optimization of medium specific speed centrifugal pump

Abstract: In this paper, a centrifugal pump of medium specific speed is taken as the research object, and the performance changes of the centrifugal pump are studied by setting five different ratio degrees of blades. The results show that due to the shortening of the blade length, the pump head and efficiency both decrease with the decrease of the ratio degree. In terms of static pressure distribution, the high pressure area in the volute expands from the outlet to the upstream with the decrease of the ratio degree, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
0
0
Order By: Relevance
“…The study showed that at high flow rates, the head and efficiency of the centrifugal pump are significantly affected by the inducer clearance, with an increase in clearance leading to an increase in head and efficiency. Wang et al [5] investigated the effect of blade geometry parameters on the performance characteristics of a centrifugal pump at medium specific speeds and found that as the length of the blades decreases, the head and efficiency also decrease. Zhao et al [6] studied the impact of different blade parameters on the external characteristics of the pump and found that within a certain range of blade thickness variation, increasing the blade thickness slightly improves the maximum efficiency of the centrifugal pump.…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that at high flow rates, the head and efficiency of the centrifugal pump are significantly affected by the inducer clearance, with an increase in clearance leading to an increase in head and efficiency. Wang et al [5] investigated the effect of blade geometry parameters on the performance characteristics of a centrifugal pump at medium specific speeds and found that as the length of the blades decreases, the head and efficiency also decrease. Zhao et al [6] studied the impact of different blade parameters on the external characteristics of the pump and found that within a certain range of blade thickness variation, increasing the blade thickness slightly improves the maximum efficiency of the centrifugal pump.…”
Section: Introductionmentioning
confidence: 99%